Introduction: a psycho-criminological understanding of animal abuse and interpersonal violence - Chan, Heng Choon (Animal abuse and interpersonal violence, 2024)
Animal abuse is a growing issue globally. It is broadly defined as socially unacceptable behavior that is intentionally perpetrated to cause unnecessary pain, suffering, distress, and/or death to an animal. Although decades of research have advanced our knowledge about animal abuse, we still have much to learn about its relationship with (subsequent) interpersonal violence against human victims. Thus, the primary objective of this edited collection is to advance our understanding by presenting up-to-date research and best practice in the field by active researchers and experienced field practitioners from six countries: the United States, the United Kingdom, France, the Netherlands, Hong Kong, and Turkey. The book takes a psycho-criminological approach to examine aspects and dynamics of animal abuse, interpersonal violence, and the perpetrators of such abuse. The book comprises 16 chapters and is divided into two parts (theory and research, and policy and practice). It introduces readers to contemporary research across a range of topics and issues related to animal abuse and interpersonal violence.